(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Stock market plays a crucial role in the financial system of a country. It can be viewed as a channel through which resources are properly channelized. It enables the governments and industries to raise long-term capital for financing new projects. The stock markets of developing economies are likely to be sensitive to various macro-economic factors such as GDP, imports, exports, exchange rates etc. When there is high demand on financial products, as a constituent of financial market, and ultimately stock market needs to develop. Many factors can be a signal to stock market participants to expect a higher or lower return when investing in stock and one of these factors are macroeconomic variables. Thus, macro-economic variables tend to affect stock market developments. Objective: This study examines the linkage between stock market prices (NEPSE index) and five macro-economic variables, namely; real GDP, broad money supply, interest rate, inflation and exchange rate using an autoregressive distributed lag (ARDL) model to explain the behavior of the Nepal Stock Exchange Index. Methods: The study uses error correction model (ECM) which is delivered from ARDL model through simple linear transformation to integrate short run adjustments with long run equilibrium without losing long run information. The analysis has been done by using 25 years’ annual data from 1994 to 2019. Findings: The result indicates that the fluctuation of NEPSE Index in long run is strongly associated with broad money supply, interest rate, inflation, and exchange rate. The GDP, money supply and exchange rate can positively define in short run while only money supply holds positive relationship in long run. Conclusion: Though Nepalese stock market is not yet well developed and matured, broad money supply, interest rate, inflation and exchange rate are major factors affecting stock market price of Nepal. Therefore, policies and strategies should be made and directed taking these into considerations. Implication: The findings of research can be helpful to understand the behavior of Nepalese stock market and develop policies for market stabilization.